MENINGKATKAN PEMAHAMAN KONSEP ASESMEN MELALUI PROSES MIND MAPPING - Siti Rohmi Yuliati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
The students of Primary Education Teachers Education of S1 in the Scool of Education, State University of Jakarta, found difficulties in understanding and implementing of assessment concept in the course of Instructional Evaluation Development. This classroom action research which was conducted in 2008, aimed at overcoming the difficulties by using mind mapping startegy. Involving 70 students of Primary Teachers Education in theShcool of Education of State University of Jakarta, the research employed developing and improving instructional quality method following the classroom action research model introduced by Standford and Kemmis. At the end of the research it wa sfound out there ia a significant improvement of the students’ understanding in the assessment concept.